2007
DOI: 10.1111/j.1469-0691.2006.01635.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics and DNA array-based genotyping of pandemic Staphylococcus aureus strains encoding Panton-Valentine leukocidin

Abstract: Within the last few years, methicillin-resistant Staphylococcus aureus (MRSA) strains encoding Panton-Valentine leukocidin (PVL) have emerged and spread worldwide. This epidemic can be attributed to a small number of distinct clones. The present study used a novel assay, based on multiplex linear DNA amplification and subsequent microarray hybridisation, to simultaneously detect all relevant exotoxins, antimicrobial resistance determinants and the allelic variants of agr. The genes of the staphylococcal exotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
101
3
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(122 citation statements)
references
References 64 publications
(94 reference statements)
15
101
3
3
Order By: Relevance
“…The agr locus belongs to the core variable genome and is thus strictly linked to CCs (33). In agreement with the findings of other studies (22,36,39), we observed that agr-1 was linked to CC8, CC22, CC45, ST7, and ST59; agr-2 was present in CC5, CC12, CC15, and ST109; agr-3 was associated with CC1 and CC30; and agr-4 was detected in CC121.…”
Section: Study Cohortssupporting
confidence: 92%
“…The agr locus belongs to the core variable genome and is thus strictly linked to CCs (33). In agreement with the findings of other studies (22,36,39), we observed that agr-1 was linked to CC8, CC22, CC45, ST7, and ST59; agr-2 was present in CC5, CC12, CC15, and ST109; agr-3 was associated with CC1 and CC30; and agr-4 was detected in CC121.…”
Section: Study Cohortssupporting
confidence: 92%
“…All MRSA isolates associated with the cluster were investigated by DNA microarray analysis using the StaphyType kit (Alere Technologies GmbH, Jena, Germany) to detect 334 S. aureus gene sequences and alleles, including antimicrobial resistance genes, virulence-associated genes, and typing markers (23). The array also assigned isolates to a multilocus sequence type (ST) and/or clonal complex (CC) and SCCmec type (25).…”
Section: Methodsmentioning
confidence: 99%
“…The emergence of CA-MRSA clones was originally thought to be continent specific, but intercontinental spread of several CA-MRSA clones has been observed and new clones have also emerged (23). Recently, a PVL-positive CA-MRSA clone, ST772-MRSA-V, that is relatively multiantibiotic resistant compared to other CA-MRSA clones was identified in several countries.…”
mentioning
confidence: 99%
“…In another study, ST152 was found to be the second most common (after ST8) clonal type among PVL-positive MRSA isolates in Austria (Krziwanek et al, 2007). In addition, Monecke et al (2007) reported a PVL-positive MRSA strain, isolated from an immigrant child from Macedonia, having ST152 clonal type and t355 spa type. Interestingly, not only PVL-positive MRSA isolates, but also PVL-positive MSSA isolates from different countries have been reported having ST152 clonal type.…”
Section: Molecular Typing Of the Strainsmentioning
confidence: 96%